Case report: Pembrolizumab as an alternative to atezolizumab following a severe infusion reaction - Lee, Seung Hyuk; Kim, Hyeon Jong; Bang, Hyun Jin; Park, Su Ji; Yu, Ji Eun; Jeong, Seung Woo; Bae, Woo Kyun (Frontiers in Oncology, 2024)
The emergence of immune-checkpoint inhibitors (ICIs) has revolutionized the field of oncology, providing promising results in various malignancies. However, ICIs can sometimes lead to severe injection reactions, requiring alternative treatment options. In this case report, we introduce a case of a severe infusion reaction induced by atezolizumab. After atezolizumab infusion, the patient experienced symptoms that were suggestive of anaphylactic shock, including chest tightness, low blood pressure, and loss of consciousness, all of which were restored by immediate administration of steroid, antihistamine, and epinephrine. When selecting a new ICI, we were concerned about cross-reactivity with atezolizumab. As such, we conducted a skin test to establish the underlying mechanism of the previous reaction to atezolizumab infusion, the results of which were highly suggestive of Ig-E-mediated hypersensitivity. The skin test for pembrolizumab, another ICI, was negative. Therefore, we replaced atezolizumab with pembrolizumab, and the infusion proceeded safely. To date, the patient has undergone 13 cycles of pembrolizumab, and the disease has remained stable. This case demonstrates that patients who exhibit severe injection reactions to ICIs can continue treatment safely, without cross-reactions, with alternative ICIs. This case will help provide patients who have experienced drug-related hypersensitivity reactions with a choice to use alternative ICIs, thus expanding their options for chemotherapy.